Ore Deposit Geology and its Influence on Mineral Exploration - Edwards, Richard. author. aut Link
XVI, 466 p.
Keywords: Why another book about Ore Deposits? There are a number of factors which motivated us to write this text and which may provide an answer to this question. Firstly our colleagues are predominantly mining engineers and minerals processing technologists, which provides us with a different perspective of ore deposits from many academic geologists. Secondly we have found that most existing texts are either highly theoretical or merely descriptive: we have attempted to examine the practical implications of the geological setting and genetic models of particular ore deposit types. We have written the text primarily for undergraduates who are taking options in Economic Geology towards the end of a Degree Course in Geology. However, we hope that the text will also prove valuable to geologists working in the mining industry. The text is to a large extent based on a review of the existing literature up to the end of 1984. However, we have visited most of the mining districts cited in the text and have also corresponded extensively with geologists to extend our knowledge beyond the published literature. Nonetheless writing a text-book on Ore Deposits is a demanding task and it is inevitable that sins of both omission and commission have been committed. We would therefore welcome comments from readers which can be incorporated in future editions. RICHARD EDW ARDS KEITH ATKINSON Cmnhome School (~n\1illcs April 1985 Glossary Adit A horizontal, or near horizontal, passage from the surface into a mme.